Najmieh Batmanglij: Silk Road Cooking: A Vegetarian Journey - Davidson, Alan (Petits Propos Culinaires, 2024)
Najmieh Batmanglij: Silk Road Cooking: A Vegetarian Journey: Mage, Washington, 2002: ISBN 0934211639: 336 pp., colour photos, h/b, 50.00.